World Report on Disability: A Call to Action - AKYÜZ, GÜLSEREN DERYA (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2012)
The World Report on Disability (WRD), a joint effort of the World Health Organization and the World Bank, is a document that presents a global picture of disability based on a best evidence synthesis available worldwide. Additionally, the WRD provides a number of recommendations, particularly for the facilitation of the implementation of the United Nations 'Convention on the Rights of Persons with Disabilities' and calls to action at national and international levels. The call to action in the WRD imposes a responsibility and obligation on the medical specialty of physical medicine and rehabilitation (PMR) with its unique approach to a health condition not only with a medical treatment perspective, but also with the perspectives of functioning and disability with the aim of improving functioning to the best possible level. The medical specialty of PMR can make substantial contributions to the implementation of the WRD, especially in the areas of specific programs and services for persons with disabilities as defined particularly in the activities and participation as well as environmental factors components of the International Classification of Functioning, Disability and Health (ICF) along with good quality scientific research. The WRD poses a challenge to promote and emphasise the value and the importance of the medical specialty of PMR. Turk J Phys Med Rehab 2012;58:255-8.
Keywords: World Report on Disability; disability; physical medicine and rehabilitation; DISTINCT SCIENTIFIC FIELDS; REHABILITATION RESEARCH; CONCEPTUAL DESCRIPTION